Variable gas density effects on transport from interacting evaporating spherical drops. (December 2018) - Cossali, Gianpietro Elvio; Tonini, Simona
Highlights: Analytical model of drop pair evaporation with variable gas density is developed. The dependence of gas mixture density on temperature/composition is considered. Analytical solution to conservation equations in bi-spherical coordinate system. Effect of drop interaction for any Lewis number is analytically quantified. Comparison with constant gas density solutions and experimental results. Abstract: The paper reports an analytical approach to model heat and mass transfer from neighbouring spherical drops accounting for the dependence of the gas mixture density on temperature and composition. The conservation equations for single-component non-identical spherical drops evaporating in gaseous quiescent environment are analytically solved in a bi-spherical coordinate system. Analytical expressions for the local heat and mass fluxes on drop surfaces and for the evaporation and the sensible heat rates are reported. The effect of relieving the commonly adopted assumption of constant gas density is quantified by comparison with existing constant density solutions for different evaporating species and operating conditions. The model applies to any value of Lewis number. Comparison with analogous results for single isolated drops allows to quantify the screening effect on vapour and heat fluxes and evaporation and heat rates.